STUDY OF GUIDANCE AND COUNSELING FOR ELDERLY: A SYSTEMATIC LITERATURE REVIEW - Mahardika, Nur; Suherman, Uman; Taufiq, Agus; Saripah, Ipah (Universitas Muria Kudus, 2024)
This study aims to describe the results of research on: trends and tendencies in research on guidance and counseling for the elderly.This study combines various perspectives to map and analyze the landscape of research on guidance and counseling for the elderly and uses 134 articles. This study was conducted in 2024 using the Scopus database as a data source. The data collection technique used was a systematic literature review to identify articles related to guidance and counseling for the elderly published in the last 10 years (2014-2024). Using the Scopus database, journals, citations, authors, and keywords were identified.This study identifies annual research trends, lists influential articles, and reveals research trends on guidance and counseling for the elderly in the last 10 years. As an innovative feature of this study, this study categorizes the identified techniques, approaches, and subjects based on their contextual dependencies to explain their reciprocal relationships. It is hoped that this study can support decision makers and practitioners in developing strategies to implement sustainable guidance and counseling for the elderly.